The Importance of Fever as a Predictive Symptom for the Potency of Host's Monocytes to Release Pro- and Anti-Inflammatory Mediators - Magdalini Kyriakopoulou; Anastasia Antonopoulou; Maria Raftogiannis; Fotini Baziaka; Thomas Tsaganos; Kyriaki Kanellakopoulou; Evangelos J. Giamarellos-Bourboulis (Mediators of Inflammation)
Objective. To clarify whether time lapsing from advent of fever as a first sign of sepsis may be indicative of the potency of monocytes for the release of pro- and anti-inflammatory mediators. Methods. Monocytes were isolated from blood of 51 septic patients and 9 healthy donors. Monocytes were incubated in the absence and presence of patients' serum and concentrations of tumour necrosis factor-alpha (TNF𝛼), interleukin (IL)-6, IL-10, and malondialdehyde (MDA) were estimated in supernatants. Patients were divided into three groups: group A: <12 hours; group B: 12–24 hours, and group C: >24 hours between initiation of fever and blood sampling. Results. TNF𝛼 of supernatants of groups B and C was higher than controls, as also were IL-6 of A and C, IL-10 of A and B, and MDA of A. IL-6 of group A was increased after addition of patients serum. A negative correlation was found between time from initiation of symptoms and IL-6 of monocyte supernatants incubated in the presence of patients serum. Median IL-6 of survivors was higher than nonsurvivors. Conclusion. Monocytes are potent for the release of pro- and anti-inflammatory mediators within the first 24 hours upon advent of fever related to sepsis; serum stimulates further release of IL-6 within the first 12 hours.